Oral nursing with Traditional Chinese Medicine solution for a patient with bad breath after acute cerebral infarction (中药口护技术治疗1例急性脑梗塞后口腔异味患者的护理体会) - MENG Yue (孟跃); GONG Xinyu (龚欣雨); GAO Bo (高波); TANG Ling (唐玲) (中西医结合护理)
This paper summarized oral nursing with Traditional Chinese Medicine solution for a patient with bad breath after acute cerebral infarction. The ingredients of Traditional Chinese Medicine (TCM) solution, operation method, cautions were introduced, and related diet nursing intervention was carried out during oral care. Based on the theory of Traditional Chinese Medicine syndrome differentiation, oral nursing with appropriate TCM solutions is potentially effective to improve the oral hygiene in the patient after acute cerebral infarction. (本文总结1例急性脑梗塞患者中药口护技术方法及护理措施, 包括中药口护的药方组成、操作方法、注意事项以及饮食护理等护理措施。基于中医辨证施护理论指导, 合理运用中药口腔护理液, 针对性采取护理措施, 能够改善急性脑梗塞患者舌苔症状和口腔异味。)